PEMANFAATAN PANEL SURYA DAN IOT UNTUK IRIGASI KEBUN PAKAN GAMA UMAMI GUNA MEWUJUDKAN KEMANDIRIAN EKONOMI BERKELANJUTAN DI KALURAHAN GIRIPURWO GUNUNGKIDUL - Zulfatun Ruscitasari; Nafiatul Umami; Irwan Novianto; Septian Rico Hernawan; Rani Agustina Wulandari; Bambang Suhartanto; Marosimy Millaty; Fajri Rahmad Dani; Dito Aji Nugroho; Duana Siska Mawardi; Amirudin Husnul Hidayat; Amelia Cahya Ramadhani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Giripurwo Village, Purwosari Subdistrict, Gunungkidul Regency, has significant potential in agribusiness and creative economy but faces geographical and infrastructural challenges, such as hilly terrain, limited water availability, and reliance on an unstable PLN electricity supply. The Kosabangsa Program was implemented to support community economic independence through the integration of renewable energy technology (EBT) and the Internet of Things (IoT), as well as the enhancement of managerial capacity and financial literacy. The program includes the implementation of a solar-powered automatic irrigation system for Gama Umami forage gardens, installation of solar panels in batik production houses, and training in simple financial bookkeeping. The results indicate improved efficiency in livestock feed production, continuity in batik production processes, and enhanced management and financial recording skills among the partners. The application of technology not only reduces operational costs but also promotes economic self-reliance and environmental awareness in the Giripurwo community. This program highlights the importance of integrating technology and community empowerment in increasing productivity and ensuring the sustainability of village enterprises.